The ballad of financial dependency: sponsoring in public health professional societies - Razum, Oliver; Bozorgmehr, Kayvan; Wenner, Judith; Weishaar, Heide (European journal of public health, 2015)
The European Public Health Association (EUPHA) has become one of the leading voices of public health in Europe. Its annual European Public Health Conference (EP